Does body mass index impact on muscle wasting and recovery following critical illness? A pilot feasibility observational study. Issue 2 (1st August 2016) - Segaran, E.; Wandrag, L.; Stotz, M.; Terblanche, M.; Hickson, M.
Abstract: Background: Critical illness is associated with muscle loss, weakness and poor recovery. The impact that illness and the ensuing metabolic response has on obese patients is not known. Objectives were to test if obese patients lose less muscle depth compared to non‐obese patients; if a reduction in muscle depth was associated with reduced strength and recovery; and to assess the feasibility of these methods with a range of body mass index's (BMI). Methods: A prospective observational pilot study of muscle depth in critically ill patients categorised by BMI was performed. Muscle depth changes were assessed by ultrasound on study days 1, 3, 5, 7, 12 and 14. Strength was measured via handgrip dynamometry and Medical Research Council (MRC) sum score on waking and at discharge from the intensive care unit. Level of dependency was measured with the Barthel index. Results: 44 critically ill patients; 17 had normal BMI, 10 were overweight and 17 were obese. The three groups did not differ in baseline characteristics, except obese patients had significantly greater initial muscle depth. Muscle depth loss was similar between the BMI groups at each of the time points. Handgrip and MRC sum score were only possible in a small number of patients because of reduced alertness and weakness. Majority were deemed fully dependent based on the Barthel index. Conclusions: Obese patients lost muscle depth in a comparable manner to non‐obese patients, suggesting that BMI may not prevent muscle depth loss. It was not possible to determine the effect on strength because the clinical condition of patients precluded reliable measurements.